2013
DOI: 10.1186/2191-219x-3-34
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of serotonin transporters with [123I]FP-CIT SPECT in the human hypothalamus

Abstract: BackgroundSerotonergic neurons in the rodent hypothalamus are implicated in key neuroendocrine and metabolic functions, including circadian rhythmicity. However, the assessment of the serotonergic system in the human hypothalamus in vivo is difficult as delineation of the hypothalamus is cumbersome with conventional region-of-interest analysis. In the present study, we aimed to develop a method to visualize serotonin transporters (SERT) in the hypothalamus. Additionally, we tested the hypothesis that hypothala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…In the hypothalamus, SERT has been shown to be ubiquitously present in controls in a postmortem human brain study (30). In line with this, PET studies using selective SERT tracers as well as an 123 I-FP-CIT SPECT study have shown specific hypothalamic binding in healthy controls (31,32). Moreover, 123 I-FP-CIT binding in the hypothalamus of rats could be blocked with an SSRI, but not with a DAT blocker (5).…”
Section: Discussionsupporting
confidence: 51%
“…In the hypothalamus, SERT has been shown to be ubiquitously present in controls in a postmortem human brain study (30). In line with this, PET studies using selective SERT tracers as well as an 123 I-FP-CIT SPECT study have shown specific hypothalamic binding in healthy controls (31,32). Moreover, 123 I-FP-CIT binding in the hypothalamus of rats could be blocked with an SSRI, but not with a DAT blocker (5).…”
Section: Discussionsupporting
confidence: 51%
“…In a second analysis, SERT binding in the hypothalamus was assessed using manually drawn ROIs on individual MRIs as described previously [22]. We used these manually drawn ROIs because it is not possible to identify the hypothalamus on SPECT images due to the limited spatial resolution.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing or decreasing serotonin signalling affects heat or cold tolerance [10,11], peristalsis [9], urine storage [12,13], and blood pressure [14]. In rodents, stimulating serotonergic neurons in the hypothalamus alters energy metabolism and cardiovascular functioning [15,16]. Dopamine has also been found to play a role in the ANS [17].…”
Section: Introductionmentioning
confidence: 99%